2017
DOI: 10.21276/ijlssr.2017.3.4.14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pulmonary Capacity and Prevalence of Pulmonary Dysfunctions of Bell Metal Workers in Relation to their work Experience and Smoking Habit

Abstract: The bell metal works is the oldest cottage industries mainly clustered around the Bankura, Purulia and Medinipur (W) districts in West Bengal, India. The smelting, hammering, scraping and paddle rolling are the most predominant activities in their Bell Metal work process. During work, different types of metal fumes are sublimated to their working environment. The present study was to investigate the prevalence of pulmonary dysfunctions of these workers. 363 workers were randomly selected of them 263 were expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…According to Naba Kumar Das, Hiranmoy Mahata, Prakash Chandra Dhara (2017) reduction in the PEFR of bell metal worker might be due to a significant reduction in expiratory capacity suggests obstruction in smaller airways which is in support of our study. (12) According to Ege Gulec Balbay, Umran Toru et al ( 2014) there was no statistically significant difference between grinding and painting worker's group in security and safety products plant, regarding the expected values of respiratory function, they also found that painting group in lock and key factory workers had more but statistically insignificant respiratory complaints. (13) In our study we found decline in all parameters of pulmonary function as FEV1, FVC and FEV1/FVC ratio especially in FEV1 in the brass factory employees suggesting pulmonary obstructive abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…According to Naba Kumar Das, Hiranmoy Mahata, Prakash Chandra Dhara (2017) reduction in the PEFR of bell metal worker might be due to a significant reduction in expiratory capacity suggests obstruction in smaller airways which is in support of our study. (12) According to Ege Gulec Balbay, Umran Toru et al ( 2014) there was no statistically significant difference between grinding and painting worker's group in security and safety products plant, regarding the expected values of respiratory function, they also found that painting group in lock and key factory workers had more but statistically insignificant respiratory complaints. (13) In our study we found decline in all parameters of pulmonary function as FEV1, FVC and FEV1/FVC ratio especially in FEV1 in the brass factory employees suggesting pulmonary obstructive abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on Car spray paint sprayers showed that subjects who were exposed to car painting vapors the pulmonary function markers were significantly decreased compared with unexposed subject [3] . In another study in Bell metal workers-exposed subjects had reduced pulmonary capacity [4] .…”
Section: Symptoms and Risk Factors In Patients Withmentioning
confidence: 92%